Circular economy approach: A sustainable business model in transforming farmers’ livelihoods - Fajar Purwanto; Soesanto Soesanto; Sari Rahayu; Zenita Afifah Fitriyani; Dimas Ganda Permana Putra (Journal of Economics Research and Policy Studies, 2026)
The transition toward a circular economy in agriculture is essential for improving resource efficiency, reducing waste, and strengthening farmers’ livelihoods. This study aims to formulate a sustainable business model based on a circular economy approach to support the transformation of farmers’ livelihoods. A qualitative descriptive case study was conducted using interviews, focus group discussions, field observations, and secondary data. The data were analyzed using SWOT, IFAS–EFAS, and TOWS matrices to identify internal and external strategic factors. The IFAS results show that strengths exceed weaknesses, with a difference of 0.415, while the EFAS results indicate that opportunities exceed threats, with a difference of 0.414. These findings place the farmers’ business position in the aggressive or SO quadrant. The key strategic insight is that farmers should prioritize market expansion for organic products, technology adoption, product differentiation, stronger partnerships, and research collaboration while gradually improving post-harvest processing, packaging, human resource regeneration, and access to financing. A circular economy-based sustainable business model is feasible for transforming farmers’ livelihoods by improving cost efficiency, product quality, supply stability, market access, and business resilience.